Fouling Polychaetes in Tanjung Priok Port of Jakarta, Indonesia - Hadiyanto Hadiyanto (ASEAN Journal on Science and Technology for Development, 2018)
Fouling polychaetes in Tanjung Priok Port, Jakarta and their status were studied in order to update the list of marine alien species in Indonesia. Polychaetes were collected using six PVC panels that were submerged at a depth of 0.5 m over three months in Jakarta Bay. Polychaetes were identified to the lowest taxon possible based on characteristics of external morphology. The geographical distribution of identified polychaetes was then determined based on taxonomic literature in order to justify whether they were native or alien species for Indonesian waters. Twelve fouling polychaetes belonging to nine families are reported here. Of these, nine species (i.e., Chrysopetalum debilis, Eunice hirschi, Ceratonereis mirabilis, Leonnates decipiens, Polyophthalmus pictus, Eulalia (Eumida) sanguinea, Lepidonotus tenuisetosus, Hydroides elegans, and Polydora ciliata) were native species, while three other taxa (i.e., Namanereis sp., Hypsicomus sp. 1, and Hypsicomus sp. 2) were undetermined.